Early Detection Policies Prevent Non-Procedural Indonesian Migrant Workers - Ida Irawati; Susanti Susanti; Sadu Wasistiono; Mani Festati Broto (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2025)
Non-procedural migration in Indonesia presents serious legal and human rights challenges, particularly in the deployment of migrant workers outside formal governance frameworks. These practices increase vulnerability to human trafficking and cause violations of fundamental rights, including inadequate health protection in host countries. This study examines the effectiveness of early detection policies in preventing non-procedural Indonesian migrant workers and proposes an alternative preventive model. The research applies a qualitative approach and analyzes data collected between November 2024 and June 2025 through document analysis and in-depth interviews using NVivo 12. The findings indicate that, first, institutions fail to coordinate effectively and allocate sufficient resources to implement early detection policies; second, village-level governments do not actively engage in prevention efforts, which limits outreach and weakens migration literacy in migrant-sending communities; and third, prospective migrant workers rely predominantly on brokers and informal networks for migration-related information. Based on these findings, this study introduces the IR-NET (Networking for Early Detection) model as a strategic innovation to strengthen early detection mechanisms and enhance the prevention of non-procedural migration.